PENGARUH METODE MEANINGFUL INSTRUCTIONAL DESIGN (MID) TERHADAP KEMAMPUAN KOGNITIF SISWA PADA MATA PELAJARAN QUR’AN HADITS KELAS X DI MAN 1 KUDUS - Achmad Abdul Azis (Jurnal Studi Islam dan Sosial, 2021)
The Meaningful Instructional Design (MID) method is a method that prioritizes learning meaningfulness and effectiveness by creating a cognitive-constructivism framework-activity conceptual framework. Students' cognitive ability is one of the domains in the taxonomy of education, Cognitive theory emphasizes how the process or efforts to optimize the ability of rational aspects or thinking abilities possessed by others. The problems of this research are as follows: 1) To what extent is the implementation of the Meaningful Instructional Design (MID) method on the subject of Qur'an Hadith class X at MAN 1 Kudus?. 2) To what extent are the students' cognitive abilities in the subject of Qur'an Hadith class X at MAN 1 Kudus?. 3) Is there any effect of the Meaningful Instructional Design (MID) method on the cognitive abilities of students in the class X Qur'an Hadith subject at MAN 1 Kudus?. This study uses a quantitative approach with data collection techniques used through questionnaires, observations, interviews and documentation of related agencies at MAN 1 Kudus. The results of this study are as follows: 1) The implementation of the Meaningful Instructional Design (MID) method on the subjects of the X Qur'an Hadith class at MAN 1 Kudus is considered to have a good influence because the results of the mean (average) questionnaire method of Meaningful Instructional Design (MID) shows a value of 80.48 from 40 respondents and is included in the interval (78-81) which is the "good" category. 2) Cognitive ability of students in the subject of Qur'an Hadith class X at MAN 1 Kudus is considered to have a good influence because the mean (average) result of the student cognitive ability questionnaire shows a score of 80.35 out of 40 respondents and is included in the interval ( 78-81) which is the “good” category. 3) There is a significant effect of the Meaningful Instructional Design (MID) method on students' cognitive abilities in the subjects of the X Qur'an Hadith class at MAN 1 Kudus by using linear regression statistical analysis one predictor found Freg = 11.75, then consulted on Ftable regression with df = 40-1-1 = 38. At the 5% significance level, the Ftable = 4.10 and at the 1% significance level the Ftable = 7.35. Then it is known that (11.75 > 7.35 > 4.10) the Freg value is above or greater than the rejection limit for both. Thus, the hypothesis that "there is a positive and significant effect of the Meaningful Instructional Design (MID) method on students' cognitive abilities in the subject of Qur'an Hadith class X at MAN 1 Kudus", is accepted both at a significance level of 5% and 1%